Stigma dan diskriminasi serta strategi koping pada orang dengan HIV dan AIDS (ODHA) di kota Medan, Sumatera Utara - Eva Kartika Hasibuan; Novita Aryani; Galvani Volta Simanjuntak (Holistik Jurnal Kesehatan, 2020)
People living with HIV/AIDS (PLWHA), battling stigma, discrimination and coping strategies  in  Medan, IndonesiaBackground: People living with HIV/AIDS have a multiple problem, PLWHA has a decreased physical abilities effect immunodeficiency, but also having a psychological and social problems also increase their burden. The health provider should be a place for PLWHA to get the right information about HIV/AIDS, but they follow to stigmatize and discriminate against them.Purpose: To describe coping PLWHA face up to stigma and discrimination in health provider.Methods: A qualitative with a descriptive phenomenological approach with population of this research was people living with HIV/AIDS (PLWHA) in Medan, Indonesia. The number of samples was of 10 respondent  by purposive sampling technique. The criteria of the sample were PLWHA get treatment for ≥ 6 months and able to communication in Indonesia is well. Data collected with in-depth interviews and analysis by  Nvivo version 12.0 trial.Result: Finding that four themes, the first; get stigmatize and discriminate from health workers, second; have a psychological impact, third; continue treatment to the health provider and fourth; Hoping in health services well.Conclusion: People living with HIV/AIDS (PLWHA) in Medan Indonesia still having a positive coping to face stigma and discrimination in health provider and they keep continue to get treatment in health provider.. Keyword: People Living With HIV/AIDS (PLWHA); Battling; Stigma; Discrimination; Coping StrategiesPendahuluan: Pelayanan kesehatan yang seharusnya menjadi tempat orang dengan HIV/AIDS mendapatkan pengobatan dan informasi yang benar mengenai penyakitnya, justru ikut menstigma dan mendiskriminasikan mereka.Tujuan: Untuk menggambarkan stigma, koping dan harapan ODHA di pelayanan kesehatan.Metode: Penelitian kualitatif dengan pendekatan fenomenologi deskriptif dengan populasinya  orang dengan HIV/AIDS (ODHA) di Kota Medan. Jumlah partisipan sebanyak 10 orang yang diambil dengan teknik purposive sampling. Pengumpulan data dengan wawancara mendalam dan data dianalisis dengan menggunakan software N.Vivo versi 12 trial.Hasil: Di dapatkan  empat  tema yaitu 1) Pernah mendapatkan stigma dan diskriminasi dari petugas kesehatan, 2) Pernah mengalalami dampak secara psikologis, 3) Tetap melanjutkan pengobatan ke pelayanan kesehatan, 4) Harapan pada layanan kesehatan.Simpulan: Orang dengan HIV/AIDS ODHA di kota Medan masih memiliki koping yang positif  dalam menghadapi stigma dan diskriminasi sehingga ODHA tetap melanjutkan pengobatan di pelayanan kesehatan.